Maternal and fetal factors contributing to neonatal outcome in Al-Tibri Medical College and Hospital (Journal of Fatima Jinnah Medical University, 2021)
Background: The study was done to identify the maternal and fetal factors contributing to neonatal outcome and to evaluate the correlation between risk factors and adverse neonatal outcome.Subjects and methods: This prospective observational study was conducted on 126 mothers and their neonates fulfilling the selection criteria at Al-Tibri Medical College and Hospital. A self-designed Performa was used to enter data of subjects. Sick neonates were referred to neonatal intensive care unit for admission and management. The results were analyzed by using SPSS version 22. A p-values
Keywords: Maternal factors; Fetal factors; Neonatal outcome